2012
DOI: 10.1021/jp304879s
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Graphenization of Hexaphenylborazine

Abstract: Synthesis of graphene that contains boron and nitrogen is still a big challenge. In this paper, we report the growth of boron (B)-and nitrogen (N)-doped graphene on a Pt(111) surface by graphenization of a novel molecule, hexaphenylborazine (HPB). We performed quantum chemical calculations for the molecule and compared the results with the photoelectron spectra. Deposition of HPB onto the heated Pt(111) substrate led to formation of the doped graphene. Incorporation of nitrogen and boron atoms to the graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…7,8 With regard to CACs, increased conductivity by electron doping as a result of N-doping is important rather than emergence of a band gap. Despite the many studies on the synthesis of N-doped graphene, [9][10][11][12][13][14][15][16][17] controlling the doping level is still a big challenge. One of the major reasons is the trade-off relationship between the degree of graphenization and the N-doping amount; the former requires a high growth temperature, while the latter decreases rapidly with temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 With regard to CACs, increased conductivity by electron doping as a result of N-doping is important rather than emergence of a band gap. Despite the many studies on the synthesis of N-doped graphene, [9][10][11][12][13][14][15][16][17] controlling the doping level is still a big challenge. One of the major reasons is the trade-off relationship between the degree of graphenization and the N-doping amount; the former requires a high growth temperature, while the latter decreases rapidly with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major reasons is the trade-off relationship between the degree of graphenization and the N-doping amount; the former requires a high growth temperature, while the latter decreases rapidly with temperature. [13][14][15][16][17] To overcome such a dilemma, a N-doping method effective still at room temperature is required. In addition, a direct N-doping method to graphene that can control the doping level has been highly anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…We have already found that monolayer graphene on Pt(111), which was grown from ethylene molecules, showed the intensity ratio of 0.034. 32 Therefore the amount of C atoms in the film deposited at 400 1C corresponds to that of a monolayer graphene.…”
Section: Growth From Methyl-formmentioning
confidence: 99%
“…27,28 We had previously conducted CVD growth of pristine and nitrogen doped graphenes on Pt(111). [29][30][31][32][33] Platinum is chemically stable and less contaminated compared to copper or other transition metals on which graphene can be grown. Pt does not need hydrogen during the CVD growth of graphene, making it possible to synthesize nitrogen doped graphene from a single source molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation